2014
DOI: 10.1080/19420676.2013.871325
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Social Impact: Building Sustainable Social Ventures at the Base-of-the-Pyramid

Abstract: This paper examines the process through which ventures scale their social impact in base-of-the-pyramid communities. A careful review of extant literature reveals two distinct modes of scaling social impact -breadth and depth scale. Drawing on a longitudinal study of Naandi and Drishtee -two exemplary social ventures in rural India -it is suggested that the depth and breadth scale develop through different processes. Each venture dynamically balances a minimum critical specification of social innovation, affor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
154
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(155 citation statements)
references
References 82 publications
(105 reference statements)
0
154
0
1
Order By: Relevance
“…While the construction industry clearly has some unique features, cultures and challenges for social enterprises, it is important to note that studies 12 Loosemore in other sectors have also identified similar problems suggesting that theories of social enterprise being developed outside construction might be of some value in understanding what happens inside construction. For example, Straith and Gismondi (2014) and Desa and Koch (2014) point to the challenges of scaling up a social enterprise, although also acknowledge that little is known about what scale actually means in the context of social enterprise and how social entrepreneurs achieve it. Indeed, in a recent survey of 439 social enterprises in Africa, only 13% were operating at scale (Monitor, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…While the construction industry clearly has some unique features, cultures and challenges for social enterprises, it is important to note that studies 12 Loosemore in other sectors have also identified similar problems suggesting that theories of social enterprise being developed outside construction might be of some value in understanding what happens inside construction. For example, Straith and Gismondi (2014) and Desa and Koch (2014) point to the challenges of scaling up a social enterprise, although also acknowledge that little is known about what scale actually means in the context of social enterprise and how social entrepreneurs achieve it. Indeed, in a recent survey of 439 social enterprises in Africa, only 13% were operating at scale (Monitor, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…This argument is expressed most clearly in the debate over the scaling of social impact (e.g. Bloom and Smith 2010;Desa and Koch 2014). , For example, Urvin, Jain, and Brown (2000) draw on their work on nongovernmental organizations in developing countries to argue that the main purpose of "scaling up" is to expand impact, rather than simply to grow larger.…”
Section: The Concept Of Growth In Social Venturesmentioning
confidence: 99%
“…This experience is generally coupled with an ability to mobilize and reconfigure resources and capabilities in pursuit of the organization's changing mission. These 'entrepreneurial adjustments' (Parker 2006;Desa and Koch 2014) in pursuit of economicallyand socially-productive opportunities (Penrose [1959(Penrose [ ] 2004Blundel, Spence, and Zerbinati 2010) are at the heart of the growth process. The narratives indicate that it is possible to identify prominent individuals who have taken on this role as in the case of LYF with an entrepreneurial chief executive.…”
Section: Entrepreneurial Experiences and Adjustmentsmentioning
confidence: 99%
“…Boyer (2015, p. 322) identifies scaling up as a diffusion pathway of grassroots innovations focusing on a scaling of a practice by referring to "application of practice beyond an activist core, to a broader audience". Desa and Koch (2014) identifies the diffusion and spread of one product or practice to greater number of users as a scaling and Staggenborg, and Ogrodnik (2015) point at different ways that transition initiatives meaningfully scale up in broadening participation and engagement of new members and supporters without compromising values and operation models.…”
Section: Understanding the Acceleration Dynamics Of Urban Sustainabilmentioning
confidence: 99%